The Moral Development of A Society: the Interrelation of Language and Cultural Heritage (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article emphasizes the important role of spiritual values and cultural heritage in the spiritualwell-being of society. Based on the values, heritage and traditions left by ancestors, each nationgrows and develops. People who are indifferent to the spiritual and cultural heritage of their ownpeople live in poverty. In such an atmosphere, indifference, anxiety, pessimistic sentimentsintensify, the struggle against oppressors is weakened, conflicts and disagreements within the nation grow.